1994
DOI: 10.1093/nar/22.15.3138
|View full text |Cite
|
Sign up to set email alerts
|

McpandFab-7: molecular analysis of putative boundaries of cis-regulatory domains in the bithorax complex ofDrosophila melanogaster

Abstract: A very large cis-regulatory region of approximately 300 kb is responsible for the complex patterns of expression of the three homeotic genes of the bithorax complex Ubx, abd-A and Abd-B. This region can be subdivided in nine parasegment-specific regulatory subunits. Recent genetic and molecular analysis has revealed the existence of two novel cis-regulatory elements Mcp and Fab-7. Mcp is located between iab-4 and iab-5, the parasegment-specific regulatory subunits which direct Abd-B in parasegments 9 and 10. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
144
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(150 citation statements)
references
References 61 publications
(76 reference statements)
2
144
0
Order By: Relevance
“…The Mcp element (28) has been shown to harbor a number of regulatory activities, including the ability to act as an insulator (7,19). We have discovered two activities of the Mcp element that are related to the regulation of intergenic transcription.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The Mcp element (28) has been shown to harbor a number of regulatory activities, including the ability to act as an insulator (7,19). We have discovered two activities of the Mcp element that are related to the regulation of intergenic transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic, transgenic, and molecular studies have identified a number of classes of distinct cis-regulatory elements within the iab regions capable of directing abdA and AbdB expression. Insulator DNAs have been identified at the boundaries of the iab8-iab7 domains (Frontabdominal-8, Fab8) (4), iab7-iab6 domains (Fab7) (5)(6)(7)(8)(9)(10), and iab5-iab4 domains (Miscadastral pigmentation, Mcp) ( Fig. 1 A) (7,11).…”
Section: E Xpression Of the Abdominal-a (Abda) And Abdominal-b (Abdb)mentioning
confidence: 99%
See 2 more Smart Citations
“…We show that two different boundary element insertions, one that contains the suppressor of Hairy-wing ½su(Hw) insulator and the other that contains the Mcp element, are able to block the activation of ap by the upstream wing enhancer. The Mcp element from the Drosophila BX-C (Karch et al 1994;Mü ller et al 1999) contains a separable boundary element and a PRE (Busturia et al 2001;Gruzdeva et al 2005), and, like the su(Hw) element, is able to mediate long-range pairing within or even between chromosomes (Sigrist and Pirrotta 1997;Mü ller et al 1999;Vazquez et al 2006). When crossed to an ap promoter deletion, both boundary inserts exhibit the interallelic complementation characteristic of transvection.…”
mentioning
confidence: 99%